Modified Asphalt - Luis Rivera-Armenta, Jose; Adriana Salazar-Cruz, Beatriz (IntechOpen, 2018)
Asphalt modification is an important area in the development of new road and pavement materials. There is an urgent demand for road materials that can minimize fracture at low temperatures and increase resistance to deformation at high temperatures. The function of asphalt is to bind aggregate to protect it from water and other harmful agents. In the beginning asphalt was ideal for this purpose, but recently traffic loads have increased and environmental factors have deteriorated more rapidly than before. Asphalt is a byproduct of crude oil in the refining process, and it is considered a complex heterogeneous mixture of hydrocarbons. Asphalt modification has become an important research area, using several methods and new materials as modifiers.